Empowering Local Economies: Training on Management and Development of Gampong-Owned Business Entity (BUMG) - Halim, Hendra; Novindra, Novindra; Maisaroh, Maisaroh; Fadhil, Rahmat; Miftahuddin, Miftahuddin; Murkhana, Murkhana; Riyaldi, Muhammad Haris (Jurnal Pengabdian Bakti Akademisi, 2024)
The community services activity aims to enhance the knowledge and skills of the management of the Community-Owned Enterprises (BUMG) in Lamteumen Timur Village, Banda Aceh, in managing and developing their businesses. The method used is a service-learning approach, where students and lecturers from Syiah Kuala University collaborate with BUMG in designing and conducting the training. Needs identification is conducted to understand the challenges faced by BUMG. Training materials are developed based on this identification, focusing on BUMG development and management strategies. The training is conducted directly for BUMG managers and local community members, with monitoring and evaluation to ensure effectiveness. The evaluation results show an improvement in the knowledge and skills of the training participants, as well as a positive impact on BUMG management. Successful BUMDes/BUMG best practice examples are also presented as inspiration. This activity is expected to serve as a model for community engagement activities in other regions.